Pengaruh Konsumsi Teh Hijau Berlebih terhadap Kesehatan Usus - Pramai Sheila Eka Khoireina; Amelia Putri Az Zahra; Azlinatul Lulu Kharolaini; Khotimah Nur Ramadhani; Liss Dyah Dewi Arini (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Green tea is widely known as a beverage rich in antioxidants with numerous health benefits. However, excessive consumption may have negative effects, particularly on gut health. This article discusses the impact of excessive green tea consumption on stomach irritation, mineral absorption disruption, gut microbiota imbalance, and caffeine-related side effects. It concludes that moderate consumption of green tea (2-3 cups per day) is safe and beneficial. Proper consumption management can maximize green tea benefits without adverse effects on gut health.